The Role of Occupational Therapy in Community-Based Programming: Addressing Childhood Health Promotion - Julie Kugel; Heather Javaherian-Dysinger; Liane Hewit (Scholarworks @ WMU, 2017)
Background: Obesity and poor health habits impact youth's health and occupational participation. Occupational therapy's role in preventing and treating obesity continues to emerge in the research literature. This article explores the impact of a community-based program emphasizing health and wellness for female youth. Methods: Five girls 11 to 13 years of age participated in the healthy occupations program. Before and after the program, the participants engaged in an individual semi-structured interview and completed the Canadian Occupational Performance Measure and the CATCH Kids Club Questionnaire. The youth participated in a focus group midprogram. Results: The participants were receptive to information regarding healthy behaviors and initiated positive health behavior changes after implementation of a 7-week healthy lifestyle community- based program. Conclusion: Occupational therapy can collaborate with community partners to provide programming focused on health promotion and prevention as part of the interprofessional approach to preventing and treating childhood obesity and building healthier communities.